Tinjauan Pustaka: Evaporator Oil Essensial - Hanad Arizal; Dan Mugisidi; Oktarina Heriani (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2025)
Evaporators with vacuum and heating systems are increasingly being used in the evaporation process of essential oils for aromatherapy due to their ability to increase efficiency without damaging the quality of volatile compounds. Their working principle is to lower the partial pressure so that the oil's boiling point can be reached at a lower temperature. Under these conditions, the active compounds in essential oils can be optimally evaporated without degradation due to excessive heat. This technology is crucial given the sensitivity of essential oils to high temperatures, as the chemical components in essential oils are highly stable. This study reviews various studies and scientific literature discussing the operating principles, system design, heat transfer characteristics, and temperature control techniques of modern evaporators. A descriptive-analytical approach was used to identify technological trends and the advantages of applying vacuum and heating systems to the aromatherapy industry. The review results indicate that this system combination increases thermal efficiency, accelerates evaporation rates, and maintains the aroma profile and chemical quality of the oil. Furthermore, the use of an automatic temperature control system improves process precision, reduces the loss of active compounds, and supports better energy efficiency compared to conventional heating methods. This technology holds great potential for the development of modern, stable, efficient, and environmentally friendly aromatherapy diffusers.